Distributed sensor and vehicle networked systems for environmental applications - João B. Sousa (2003)
The recent and exciting possibilities offered by the operation of networked vehicles and distributed sensor systems are reviewed and their applications in environmental field studies are outlined. Networked vehicle systems involving sea, air, and ground autonomous or operator-assisted vehicles are used as platforms for active sensing, such as adaptive sampling for oceanographic field studies.Sensor networks combine data from spatially distributed sensor units which in addition to sensing capabilities have processing, power management, and communication capabilities. The cost of these sensor units is already in the order of some Euros and it is expected to reduce even further in a near future. This allows for the deployment of a high concentration of sensor units in a fairly large geographical area with acceptable costs. The combined operation of networked vehicles and sensor units allows researchers to envision ambitious environmental studies where, for example, a given geographical is monitored in real-time with adjustable resolution.The review is done in the context of the research programme of the Underwater Systems and Technology Laboratory (USTL) from Porto University. Over the last two years the USTL devoted an intense effort to the development of feasible concepts for the networked operation of multiple vehicles and systems, and the first deployments are scheduled for late 2003.